Xanthogranulomatous Pyelonephritis With Emphysematous Pyelonephritis: A Case of Two Unusual Variants in One Patient - Ifeoma P. Kwentoh; Areeg Ahmed; Olugbenga Salako; Fatima Anwer; Oluwole Konigbagbe; Suhaib Andrabi; Leroy Herbert (Annals of Internal Medicine: Clinical Cases)
Xanthogranulomatous pyelonephritis (XGPN) and emphysematous pyelonephritis (EPN) are both rare forms of aggressive pyelonephritis that are associated with chronic urinary tract obstruction and recurrent urinary tract infection. Emphysematous pyelonephritis is characterized by necrotizing gas foci. Both have an abysmal prognosis. This report describes a 64-year-old woman presenting with acute gross hematuria and left flank pain after a flu-like illness. Diagnostic computed tomography of the abdomen identified both a right renal “bear paw sign” consistent with XGPN and multiple gas foci with air-fluid levels in the left kidney, pathognomonic of EPN. Fewer than 10 such cases of concurrence have been reported.